Distributions and threats of red kites (Milvus milvus) breeding in southern Sweden - Soutkari,Anna (2025)
In a world of rapid biodiversity loss, raptors are vulnerable due to their longevity and low reproductive rates. The red kite (Milvus milvus) is one of few migratory raptors breeding exclusively in Europe. It has previously experienced steep population declines caused mainly by persecution but mostly recovered, no longer classified as globally endangered. However, negative population trends persist regionally and the species’ distribution range is shifting northward. In Sweden, the population recovery has been remarkable. Formerly an exclusively migratory species, now a significant proportion winter in Sweden. Most migrating individuals are juveniles. The purpose of this study was to monitor a population of red kites in Skåne, where the Swedish red kites are concentrated. This was done through counts of communal winter roosts and mapping of nests within a study area. I also studied causes of death from ringing recoveries. Roosts were similar to previous counts in the province. No influence of temperature was found, with declining numbers rather associated with the approach of the breeding season. Most observed birds at roosts were of unknown age, though adults more numerous in line with documented migration strategies. The breeding density found in the study area was very high for the species, which suggests that conditions are favourable. The number of chicks/nest was somewhat low, but it was unconfirmed whether this was due to density dependent regulation. Anthropogenic causes dominated known causes of death. Causes varied for recoveries within and outside Sweden, and thus for juveniles and adults due to variation in migration strategies. The ringing data emphasised the danger of persecution that migrating red kites were exposed to in past decades, which remains a problem in parts of the distribution. Other threats include poisonings, collisions and deaths due to electricity structures, as well as agricultural intensification and the emerging threat of climate change. Going forward, Swedish red kites play an increasingly large role for the global population.